2021
DOI: 10.2147/dmso.s309400
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Different Obesity Patterns and the Risk of Developing Type 2 Diabetes Mellitus Among Adults in Eastern China: A Cross-Sectional Study

Abstract: Purpose Obesity has become a public health challenge worldwide and can lead to the development of diabetes. However, studies examining the associations between different obesity patterns and the development of type 2 diabetes mellitus (T2DM) in China are limited. Therefore, this study aimed to explore the associations between three obesity patterns and the risk of T2DM development in Eastern China. Methods A cross-sectional study was conducted at our health examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Another important effect is the occurrence of cardiovascular disease, which increases morbidity and mortality. 6,7,9,20 Obese children may have risk factors detrimental to cardiovascular health with cardiovascular comorbidities such as dyslipidemia, which manifests as an increase in lowdensity lipoprotein (LDL) levels. 2,3,6 Previous studies have also reported a direct relationship between body mass index and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another important effect is the occurrence of cardiovascular disease, which increases morbidity and mortality. 6,7,9,20 Obese children may have risk factors detrimental to cardiovascular health with cardiovascular comorbidities such as dyslipidemia, which manifests as an increase in lowdensity lipoprotein (LDL) levels. 2,3,6 Previous studies have also reported a direct relationship between body mass index and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,9,20 Obese children may have risk factors detrimental to cardiovascular health with cardiovascular comorbidities such as dyslipidemia, which manifests as an increase in lowdensity lipoprotein (LDL) levels. 2,3,6 Previous studies have also reported a direct relationship between body mass index and cardiovascular disease. 18,28,31 Abdominal circumference (central obesity) is not only related to body mass index; it also influences the occurrence of metabolic disorders, which are related to the occurrence of type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations